La naissance d’un écrivain national : perspectives et enjeux — le cas de Natsume Sôseki (1867-1916) - Dan Fujiwara (Les Cahiers de Framespa)
Few people in Japan contest the idea that Natsume Soseki (1867-1916) is a “national writer.” Why is this, when he was isolated from both the main literary movements of his time as well as official government discourses? This paper aims to describe and analyze how Soseki’s works achieved a large readership during the twentieth century. It all started with the formation of a community of readers who were Soseki’s disciples. They created a coherent and idealized image of their “master” and applied a moralizing interpretation to his novels, while carefully establishing the perfect link between the two elements. The master-disciple relationship was essential because it was Soseki’s disciples who took advantage of the radical transformation of publishing circles to achieve a wider distribution. However, they also successfully incorporated Soseki’s works into secondary education – vital for transmitting and reproducing the image of their “icon”, which would later become a national one.